Uso de estrategias de motivación en la enseñanza de matemáticas de los docentes de Unidad Educativa “Pío López” de Tungurahua periodo mayo 2021- octubre-2021 - Chacaguasay Guamán, Rosendo (2022)
The objective of this research was to determine the motivational strategies used by the teachers of the Pío López Educational Unit in Tungurahua during the period May 2021-October-2021 in the teaching of mathematics. A nonexperimental descriptive, bibliographic and field design was used. It worked with a population of 20 teachers. The technique used is the survey of teachers, with a questionnaire consisting of 13 items. It was concluded that; teachers, being the ones who guide learning, must prioritize the proper use of strategies, awakening the desire for research and the proper use of technology, in addition to the intrinsic factors that motivate teachers to develop skills and abilities to teach mathematics is personal satisfaction, passion for numbers, enthusiasm and enjoyment of what is done and the extrinsic factors that motivate teachers to each mathematics is to develop the ability of logical and abstract thinking, deductive reasoning to arouse the interest of students generating self-confidence in the active search and practice of solutions in the reality they live through empathy.